AI Regulation and Its Social Impacts on Public Policy - Bukhari, Syed Rizwan Haider; Khan, Haider Ali; Rebhi, Tourkia (Regional Lens, 2026)
Artificial intelligence (AI) is not a marginalized technological means any more but the main force of decision-making in political arenas, economic restructuring, and social change. The necessity to establish routine regulation frameworks has become especially relevant, with governments introducing AI-based systems into various areas of state business such as welfare checks and predictive policing, health-care screening, and taxing. The effects of AI control on the policy outcomes of a population will be examined in terms of the social influence of algorithmic governance, the dispositional capacity of a state, institutional responsibility, and trust in citizens. The tension between innovation, rights protection and state power has been identified as a qualitative evaluation of the critiques in the presence of the good arguments and other accessible resources of law, scholarship and policy and practice in democratic and hybrid political regimes and developing political regimes. The results show that unless carefully monitored apply AI, it becomes the origin of institutional transparency, discrimination, and worse democratic participation, yet attentive regulation systems can reestablish order in the service provision practice, enhancing transparency profile and offering equitable governance. This paper conclusively gives the recommendations regarding the rights based regulatory frameworks, the stronger oversight organizations and participatory policymaking frameworks that would focus on the technology developments and the social welfare.